Experimental and simulation validation of ABHE for disinfection of Legionella in hot water systems. (April 2017) - Altorkmany, Lobna; Kharseh, Mohamad; Ljung, Anna-Lena; Staffan Lundström, T.
Highlights: ABHE system can supply a continues thermal treatment of water with saving energy. Mathematical and experimental validation of ABHE performance are presented. EES-based model is developed to simulate ABHE system. Energy saving by ABHE is proved for different initial working parameters. Abstract: The work refers to an innovative system inspired by nature that mimics the thermoregulation system that exists in animals. This method, which is called Anti Bacteria Heat Exchanger (ABHE), is proposed to achieve continuous thermal disinfection of bacteria in hot water systems with high energy efficiency. In particular, this study aims to demonstrate the opportunity to gain energy by means of recovering heat over a plate heat exchanger. Firstly, the thermodynamics of the ABHE is clarified to define the ABHE specification. Secondly, a first prototype of an ABHE is built with a specific configuration based on simplicity regarding design and construction. Thirdly, an experimental test is carried out. Finally, a computer model is built to simulate the ABHE system and the experimental data is used to validate the model. The experimental results indicate that the performance of the ABHE system is strongly dependent on the flow rate, while the supplied temperature has less effect. Experimental and simulation data show a large potential for saving energy of this thermal disinfection method by recovering heat. To exemplify, when supplying water at a flow rate of 5 kg/min and at a temperature of 50 °C, the heat recovery is about 1.5 kW while the required pumping power is 1 W. This means that the pressure drop is very small compared to the energy recovered and consequently high saving in total cost is promising.